Template-oriented synthesis of monodispersed SnS2@SnO2 hetero-nanoflowers for Cr(VI) photoreduction - Zhang, Xi; Zhang, Peng; Wang, Lijie; Gao, Hongqing; Zhao, Jiangtao; Liang, Changhao; Hu, Junhua; Shao, Guosheng (Applied catalysis. B, Environmental, 2016)
We firstly reported a template-oriented method to fabricate mono-dispersed SnS2@SnO2hetero-nanoflowersforCr(VI) photoreduction. [Display omitted] •Template-oriented Synthesis of SnS2@SnO2 hetero-nanoflowers.•Nanoflowers showed enhanced photocurrent and photocatalytic performance.•Easy photocatalyst separation and reuse. The controlled chemical conversion of nanomaterials represents an important basis for both understanding the nanoscale chemical activity and exploring new desirable materials. In this work, the region selective ion-exchange transformation of one-dimensional (1D) SnO2 nanotubes (SNT) into three-dimensional (3D) SnS2@SnO2 nanoflowers (SNF) were prepared by combining the electrospinning technique and hydrothermal method. The template-oriented synthesized SnS2@SnO2 demonstrated good dispersibility and uniformity, which can be proved by field-scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM). Compared with SNT, SNF showed an improved visible light harvest even to the near-infrared light region through Ultraviolet-Visible Spectroscopy (UV–vis). What's more, SNF showed enhanced water purification performance for oxalic acid-induced photocatalytic reduction of Cr(VI) under visible light irradiation at room temperature, which could be attributed to the staggered band alignment formed between the two semiconductors. Besides, the corresponding mechanism of enhanced photocatalysis regarding the separation of the photogenerated electron-hole pairs for the heterojunction has also been investigated through photoluminescence spectroscopy (PL) and photocurrent analysis.